STUDENT TO SELF-FEEDBACK IN IMPROVING STUDENTS’ SPEAKING ABILITY - Rizka Indahyanti; Mutmainnah Mursidin (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2017)
This research is basically aimed to test the Student to the self-feedback method in improving their speaking ability. Furthermore, it is aimed to see the effectiveness of colleagues in helping other friends to learn. The method used in this research is the Quantitative method with the quasi-experimental setting in its test. The step of this research includes the field observation, pre-test, giving treatment by applying student to the self-feedback method, then post-test. One by one the student talks then another friend judge what the strengths and the weaknesses of his friend. The instruments used in this research are speaking test and questionnaire. The written assessment contained in the assessment aspect includes fluency, accuracy, and comprehensibility. The population in this research is all English education students of FKIP UIM. While the sample used is the second-semester students. The researchers divided the class into 2 groups. One group as the experimental class and the other as the control class.The results of the data analysis show that the probability is less than 0.05 or 0.000 0.05. This means that H1 is acceptable and, of course, the statistical hypothesis H0 is rejected. Therefore, it can be concluded that the use of Student to self-feedback method improves their speaking ability. Keywords: Students self-feedback, speaking ability